Multi-ancestry genome-wide association study of kidney cancer identifies 63 susceptibility regions - Purdue, Mark P; Dutta, Diptavo; Machiela, Mitchell J; Gorman, Bryan R; Winter, Timothy; Okuhara, Dayne; Cleland, Sara; Ferreiro-Iglesias, Aida; Scheet, Paul; Liu, Aoxing; Wu, Chao; Antwi, Samuel O; et al. (Nature genetics, 2024)
Here, in a multi-ancestry genome-wide association study meta-analysis of kidney cancer (29,020 cases and 835,670 controls), we identified 63 susceptibility regions (50 novel) containing 108 independent risk loci. In analyses stratified by subtype, 52 regions (78 loci) were associated with clear cell renal cell carcinoma (RCC) and 6 regions (7 loci) with papillary RCC. Notably, we report a variant common in African ancestry individuals ( rs7629500 ) in the 3' untranslated region of VHL, nearly tripling clear cell RCC risk (odds ratio 2.72, 95% confidence interval 2.23-3.30). In cis-expression quantitative trait locus analyses, 48 variants from 34 regions point toward 83 candidate genes. Enrichment of hypoxia-inducible factor-binding sites underscores the importance of hypoxia-related mechanisms in kidney cancer. Our results advance understanding of the genetic architecture of kidney cancer, provide clues for functional investigation and enable generation of a validated polygenic risk score with an estimated area under the curve of 0.65 (0.74 including risk factors) among European ancestry individuals.
Keywords: nádory ledvin; nádorový supresorový protein VHL; Genetic Predisposition to Disease; karcinom z renálních buněk; běloši; Kidney Neoplasms; Genome-Wide Association Study; Case-Control Studies; jednonukleotidový polymorfismus; White People; lokus kvantitativního znaku; Von Hippel-Lindau Tumor Suppressor Protein; Polymorphism, Single Nucleotide; lidé; studie případů a kontrol; Quantitative Trait Loci; Humans; Carcinoma, Renal Cell; genetická predispozice k nemoci; celogenomová asociační studie